Budaya Mutu Akademik di Fakultas Ilmu Pendidikan Universitas Negeri Makassar - Ansar Ansar; Andi Mappincara; Syamsurijal Basri (Seminar Nasional LP2M UNM, 2019)
Abstract. This study examines the culture of academic quality at the Faculty of Education, Makassar State University with the focus of the study being: (1) General description of academic quality culture; (2) The leadership strategy in developing an academic quality culture; (3) Supporting and inhibiting factors in its implementation. This study uses a qualitative approach to the type of expansiatory research. Sources of data in this study were faculty leaders, department leaders, lecturers, and students. Data collection techniques in the form of observation and in-depth interviews. Data analysis techniques are data reduction, data exposure and conclusion drawing or data verification. Checking the validity of the data is done by triangulating techniques and sources. The results showed that (1) The cultural picture of academic quality including lecturing activities carried out had not fully referred to the semester learning plans and operational standards. For reference and literacy culture has not been supported by the availability of adequate library facilities and internet networks. Scientific activities are carried out on a scheduled basis such as national and international seminars and workshops, character development and student creativity programs; (2) Strategies and policies that have been carried out by leaders at both the department level and faculty level refer to the vision and mission. The programs implemented include training in the development of instructional media for lecturers, workshops, publication of scientific papers, and the provision of learning facilities to support the lecture process. (3) Supporting factors are the competence of existing human resources that are adequate and understand their respective duties and duties, there is support from the academic community to faculty leaders so that all policies can be implemented and implemented properly. The inhibiting factor is the presence of several lecturers who get additional assignments outside so as to hamper lectures, facilities and infrastructure that are still limited such as inadequate lecture rooms and some learning facilities such as LCDs and laboratory equipment Keywords: Academic Culture, Quality